Environmental Aesthetics and Rewilding. (1st February 2017) - Prior, Jonathan; Brady, Emily
Abstract : This paper explores the practice of rewilding and its implications for environmental aesthetic values, qualities and experiences. First, we consider the temporal dimensions of rewilding in regard to the emergence of particular aesthetic qualities over time, and our aesthetic appreciation of these. Second, we discuss how rewilding potentially brings about difficult aesthetic experiences, such as the unscenic and the ugly. Finally, we make progress in critically understanding how rewilding may be understood as a distinctive form of ecological restoration, while resisting the assimilation of rewilding into wilderness discourses.